KERAGAMAN AKTIVITAS ANTIFUNGI BIOTA LAUT TERHADAP Fusarium oxysporum f.sp. vanillae, PENYEBAB BUSUK BATANG VANILI - I Ketut Suada (Bumi Lestari Journal of Environment, 2012)
The diversity of marine biota resources is very high, therefore it is necessary to be recovered for our life need. The objective of this research is to know the antifungal ability of marine biota derived from Bali Island against Fusarium oxysporum f. sp. vanillae. Samples were collected at the intertidal zone of seven beaches around Bali. Extraction of antifungal substance of raw material extract was conducted using various organic solvents until the best ability was obtained. The dry material extract was then screened using well diffusion method. The method was also used to determine the inhibition indicators to Fusarium. The methanolic extract of Aglaophenia sp. marine animal was able to suppress the Fusarium effectively, with minimum inhibition concentration (MIC) of 0.05%. The extract inhibited the colony growth, total of conidial forming, total of growing colony, total of mycelial dry weight, total of mycelial protein, however, increased fusaric acid production of the pathogen.